Multicultural Da'wah in The Charter of Medina Concept and Implementation in Indonesia - Mahbub Junaidy (CV. Syntax Corporation Indonesia, 2023)
The Medina Charter was the first written constitution established by the Prophet Muhammad as a rule or legal system to regulate social relations in Medina between Muslims and non-Muslims. The Prophet Muhammad (peace be upon him) used a variety of approaches in the formation of this charter of Medina. The principles of tolerance, simplicity, equality, and equality were held by the Prophet Muhammad in forming the Medina Charter. Because, the Medina Charter became the basis for social processes concerning the life of the people of Medina at that time in various aspects of life, both social, religious, cultural, economic, and political life. In the context of the Indonesian nation which is very diverse in national culture, language, customs and even religious beliefs, the author feels the need to raise this research study in the perspective of Multicultural Da'wah Medina Charter in Indonesia with the approach taken by the Islamic Organization in Indonesia, namely Nahdatul Ulama'. In this study, qualitative analysis methods with various approaches point of view, including historical, cultural, experiential and psychological approaches to society are very diverse. The concept of Multicultural da'wah is a very effective da'wah approach in Indonesian society which is very diverse, both cultural, linguistic, customary and diversity of beliefs, so that the principles of the Medina charter are very appropriate and relevant and can be used as a reference in the development of da'wah in Indonesia. The implementation of multicultural da'wah carried out by Nahdlatul Ulama' in Indonesia can be an example as a competent, appropriate and effective da'wah institution in the development of da'wah in our beloved homeland, Indonesia